Magnetically drivable nano-bio-conjugate mimicking free curcumin redox behavior - Magro, Massimiliano; Campos, Rene [UNESP]; Baratella, Davide; Lima, Giuseppina Pace Pereira [UNESP]; Zboril, Radek; Vianello, Fabio (Tanger Ltd, 2014)
Curcumin possesses wide-ranging anti-inflammatory and anti-cancer properties and its biological activity can be correlated to its potent antioxidant capacity. Novel maghemite (gamma-Fe3O4) nanoparticles, characterized by a diameter of about 10 nm and possessing peculiar colloidal properties and surface interactions, called Surface Active Maghemite Nanoparticles (SAMN), were superficially modified with curcumin by simple incubation, due to the presence of under-coordinated Fe(III) atoms on nanoparticle surface. The resulting curcumin-modified SAMNs (SAMN@curcumin) were characterized by transmission electron microscopy (TEM), FTIR, Mossbauer, EPR and UV-Vis spectroscopy. The redox properties of bound curcumin were tested by electrochemistry. Finally, SAMN@curcumin was studied in the presence of different electroactive substances, namely hydroquinone, NADH and ferrocyanide, in order to assess its electrochemical behavior. Moreover, SAMN@curcumin was electrochemically tested in the presence of one of the most diffuse reactive oxygen specie, such as hydrogen peroxide, demonstrating its stability. SAMN@curcumin in which curcumin is firmly bound, but still retaining its redox features represents a feasible adduct: a magnetically drivable nano-bio-conjugate mimicking free Curcumin redox behavior. The proposed nanostructured material could be exploited as magnetic drivable curcumin vehicle for biomedical applications.
Keywords: Curcumin; Maghemite nanoparticles; Nanomaterial electrocatalysis; Hydrogen peroxide; NADH oxidation